Webinar Insights: Policy implications for the growing supply and demand of nutrient-dense foods in Africa - Nguyen, Vi (International Food Policy Research Institute, 2023)
The supply and demand of fruits, vegetables and animal products is often insufficient and too expensive for most consumers in sub-Saharan Africa. However, recent evidence suggests that both the production and consumption of these nutrient-dense products is rapidly growing. What are the policy implications of this? And what can governments do to stimulate more inclusive and sustainable domestic value chains?